Process for the preparation of a zirconia granulation powder with low chloride content

CN118324516BActive Publication Date: 2026-10-23WANHUA CHEM GRP BATTERY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310007220.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-04
Publication Date
2026-10-23
Estimated Expiration
2043-01-04

AI Technical Summary

Technical Problem

但是采用液相法制备锆前驱体浆料时,液相中含有大量的氯离子极容易吸附在前驱体表面形成盐桥,使前驱体产生了大量的软团聚包裹氯离子,这使得氯离子在后续的洗涤过程中很难脱除而留在了锆的前驱体中,同时氯离子也很难在后续的高温煅烧中被排出,而造粒粉中氯离子杂质将显著降低氧化锆制品的强度和透光度

Benefits of technology

[0021]本发明的制备方法,先控制液相合成条件减少氯离子包裹,再用真空带式过滤机洗涤滤饼以脱除游离的氯离子,干燥、焙烧制得氧化锆粉体,最后加水制浆并通入二氧化碳,进一步洗涤脱除吸附在氧化锆颗粒表面的氯离子,该方法简单高效、环保且操作成本低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004036090980000061
    Figure BDA0004036090980000061
Patent Text Reader

Abstract

The application discloses a preparation method of zirconium oxide granulation powder with low chloride ion content, and comprises the following steps: firstly, the aqueous solutions of zirconium oxychloride, yttrium chloride and a precipitant are simultaneously added into a reaction kettle at a certain flow rate for reaction, then loose spherical precursor powder is obtained through washing and drying, the powder is mixed with pure water again after calcination, carbon dioxide is introduced for stirring and washing, then solid-liquid separation is carried out, and finally sand grinding and granulation are carried out to obtain the granulation powder. The application solves the problems of poor chloride ion removal effect, high cost and large wastewater pollution in the existing liquid phase method for preparing zirconium oxide granulation powder. The preparation method is simple, efficient, environment-friendly and low in cost, and the chloride ion content in the granulation powder is less than 10 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic material preparation, specifically relating to a method for preparing zirconia granulated powder with low chloride ion content. Background Technology

[0002] Zirconia granulated powder ceramic products possess excellent properties such as high strength and high light transmittance, and are widely used in structural ceramics such as bearings and abrasives, as well as functional ceramics such as mobile phone back panels and dental components. The conventional preparation steps for zirconia granulated powder are: 1) Using zirconium oxychloride as raw material and yttrium chloride as a stabilizer, a zirconium precursor slurry is prepared through methods such as co-precipitation, hydrolysis precipitation, sol-gel method, and hydrothermal method; 2) Zirconia powder is obtained through filtration, drying, and calcination; 3) Finally, the granulated powder is obtained through sand milling. However, when preparing the zirconium precursor slurry using the liquid phase method, the large amount of chloride ions in the liquid phase easily adsorbs onto the precursor surface, forming salt bridges. This causes the precursor to produce a large number of soft agglomerates that encapsulate chloride ions, making it difficult to remove them during subsequent washing and leaving them in the zirconium precursor. Furthermore, chloride ions are difficult to remove during subsequent high-temperature calcination. The chloride ion impurities in the granulated powder significantly reduce the strength and light transmittance of the zirconia products.

[0003] To overcome the above problems, patent CN1743272A uses ultrafiltration membrane separation technology to remove chloride ions from nano-zirconium dioxide (ZrO2) hydrate particle system, but it requires specific filtration equipment and the filter element needs to be replaced frequently, resulting in high operating costs; patent CN101074116B uses methanol or ethanol to wash chloride ions to prepare monodisperse ultrafine zirconium dioxide, but the wastewater generated by this method contains organic solvents, which is not environmentally friendly. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing zirconia granulated powder with low chloride ion content, thereby reducing the chloride ion content.

[0005] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:

[0006] A method for preparing zirconia granulated powder with low chloride ion content includes the following steps:

[0007] (1) Prepare an aqueous solution containing zirconium salt, yttrium salt and precipitant, and then add the three solutions to the reaction vessel at a certain flow rate. Adjust the linear speed of the stirrer, and after the reaction is completed, age the mixture to obtain a white slurry.

[0008] (2) The white slurry was washed and spray-dried to obtain a loose and porous precursor powder, which was then calcined at high temperature to obtain zirconium oxide powder;

[0009] (3) Add a certain proportion of zirconium oxide powder and pure water into a high-speed mixing tank, and simultaneously introduce carbon dioxide gas into the solution to stir and wash the powder. Then let it stand to separate the supernatant, and finally add pure water to obtain zirconium oxide slurry.

[0010] (4) The zirconium oxide slurry is sand-milled and spray-granulated to obtain zirconium oxide granulated powder with low chloride ion content.

[0011] In a specific implementation scheme, the zirconium salt mentioned in step (1) is selected from at least one of zirconium oxychloride, zirconium nitrate, zirconium sulfate, etc., preferably zirconium oxychloride; the yttrium salt is selected from at least one of yttrium chloride, yttrium nitrate, yttrium sulfate, etc., preferably yttrium chloride; the precipitant is selected from at least one of ammonia, urea, ammonium carbonate or ammonium bicarbonate, etc., preferably ammonia.

[0012] In one specific implementation, the molar ratio of the aqueous solutions of zirconium salt, yttrium salt and precipitant in step (1) is 1:0.03-0.1:2-5; preferably, the linear velocity of the stirrer is 2-6 m / s, the aging temperature is 75-95℃, and the aging time is 1-4 h.

[0013] In one specific implementation, the washing medium in step (2) is pure water, the washing temperature is 70-90℃, and the volume ratio of the washing medium to the slurry is (1-4):1.

[0014] In one specific implementation, the washing equipment used in step (2) is a vacuum belt filter, and the filter cake thickness during washing is 0.1-1cm.

[0015] In one specific implementation, the spray drying temperature in step (2) is 200-250°C; preferably, the precursor powder obtained after drying is a loose and porous spherical particle with an average particle size of 30-150 μm.

[0016] In one specific implementation, the high-temperature calcination temperature in step (2) is 1150-1300℃, and the calcination time is 4-8h.

[0017] In one specific implementation, the mass ratio of zirconium oxide powder to pure water in step (3) is (0.2-2):1, and the temperature of the pure water is 70-90℃.

[0018] In a specific implementation plan, carbon dioxide gas needs to be introduced in step (3) at a flow rate of 5-10 L / min, while the stirring time is 5-30 min and the settling time is 0.5-4 h.

[0019] In one specific implementation, the chloride ion content in the zirconia granulated powder obtained in step (4) is less than 10 ppm.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The preparation method of the present invention first controls the liquid phase synthesis conditions to reduce chloride ion encapsulation, then washes the filter cake with a vacuum belt filter to remove free chloride ions, and then dries and calcines to obtain zirconium oxide powder. Finally, water is added to make a slurry and carbon dioxide is introduced to further wash and remove chloride ions adsorbed on the surface of zirconium oxide particles. This method is simple, efficient, environmentally friendly and has low operating costs.

[0022] The zirconia granulated powder prepared by the method of the present invention has a chloride ion content of less than 10 ppm. Detailed Implementation

[0023] The technical solution of the present invention will be further described below with reference to specific embodiments. The embodiments provide specific implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.

[0024] A method for preparing granulated zirconium oxide powder with low chloride ion content, the method comprising the following steps:

[0025] (1) First, prepare an aqueous solution of 1 mol / L zirconium oxychloride, 0.75 mol / L yttrium chloride and 2 mol / L precipitant. Use a diaphragm pump to add the three solutions into the reaction vessel at a certain flow rate. Adjust the linear speed of the stirrer. After the reaction is completed, age the mixture to obtain a white slurry.

[0026] (2) The white slurry was washed, filtered, and spray-dried multiple times to obtain a loose and porous precursor powder, which was then calcined at high temperature to obtain zirconium oxide powder.

[0027] (3) Add a certain proportion of zirconium oxide powder and pure water into a high-speed mixing tank, and simultaneously introduce carbon dioxide gas into the solution to stir and wash the powder. Then let it stand to separate the supernatant, and finally add pure water to obtain zirconium oxide slurry.

[0028] (4) The zirconium oxide slurry is sand-milled and spray-granulated to obtain granulated powder.

[0029] In step (1) of this invention, the aqueous solutions of zirconium salt, yttrium salt, and precipitant must be added to the reactor simultaneously, and the feed flow rates are adjusted to 92 ml / min, 3.68-12.27 ml / min, and 96-265 ml / min, respectively. The molar ratio of the aqueous solutions of zirconium salt, yttrium salt, and precipitant is controlled to be 1:0.03-0.1:2-5. The linear velocity of the stirrer is 2-6 m / s, such as 2 m / s, 3 m / s, 4 m / s, 5 m / s, 6 m / s, etc., to control the nucleation rate, system viscosity, and slurry dispersion effect, and to reduce the problem of soft agglomeration encapsulating chloride ions during liquid-phase synthesis. In this step, the aging temperature is 75-95℃, such as including but not limited to 75℃, 80℃, 85℃, 90℃, and 95℃, and the aging time is 1-4h, such as including but not limited to 1h, 2h, 3h, and 4h.

[0030] In step (2) of this invention, the washing medium is pure water, and the washing temperature is 70-90℃, for example, including but not limited to 70℃, 75℃, 80℃, 85℃, and 90℃. High-temperature water can maintain the viscosity of the system, increase the Brownian motion between particles, and accelerate the removal of chloride ions from the slurry. The volume ratio of the washing medium to the slurry is 1-4, for example, 1:1, 2:1, 3:1, 4:1, etc. The higher the ratio of high-temperature water to slurry, the more thorough the chloride ion washing.

[0031] In step (2) of this invention, the washing equipment used is a vacuum belt filter, which can adjust the thickness of the filter cake to control the washing effect. The thickness of the filter cake during washing is 0.1-1cm, for example 0.1cm, 0.2cm, 0.3cm, 0.4cm, 0.5cm, 0.6cm, 0.7cm, 0.8cm, 0.9cm, 1cm.

[0032] In step (2) of this invention, the spray drying temperature is 200-250℃, including but not limited to 200℃, 210℃, 220℃, 230℃, 240℃, and 250℃. The precursor powder obtained after drying is a loose and porous spherical particle with an average particle size of 30-150μm. After the first step of water washing, chloride ions are still present in the precursor powder. After drying, particles with a loose and porous structure are obtained. This structure provides a chloride ion migration channel, which is more conducive to the migration of chloride ions to the particle surface and volatilization during calcination.

[0033] In step (3) of this invention, the high-temperature calcination temperature is 1150℃~1300℃, for example, including but not limited to 1150℃, 1200℃, 1250℃, 1300℃, and the calcination time is 4h~8h, for example, 4h, 5h, 6h, 7h, 8h, etc. The zirconia powder obtained after calcination still contains a small amount of chloride ions, which can be further removed by adding high-temperature water and passing carbon dioxide. The mass ratio of zirconia powder to pure water is 0.2-2, for example, 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, etc., and the pure water temperature is 70-90℃, for example, including but not limited to 70℃, 75℃, 80℃, 85℃, 90℃, and the number of times of washing with water is 1-4 times, for example, 1 time, 2 times, 3 times, 4 times.

[0034] In step (3) of the present invention, the purity of the carbon dioxide introduced is 95-99.9%, the gas pressure is 0.1-0.3 MPa, for example, the flow rate is 5-10 L / min, the stirring time is 5-30 min, and the standing time is 0.5-4 h.

[0035] In step (4) of this invention, the chloride ion content in the granulated powder is less than 10 ppm.

[0036] The present invention will be further explained and illustrated below through more specific embodiments, but these do not constitute any limitation.

[0037] The main raw materials used in the examples are from the following sources:

[0038]

[0039] The method for testing chloride ion content is as follows: First, weigh 10g of zirconia granulated powder, then add 10ml of pure water and concentrated nitric acid respectively, dissolve at 120℃ for 30min, then filter and make up to 100ml, and finally use a chloride ion analyzer to test the content.

[0040] Example 1

[0041] First, prepare an aqueous solution of 1 mol / L zirconium oxychloride, 2 mol / L ammonia and 0.75 mol / L yttrium chloride. Turn on the stirrer and adjust the linear speed of the stirrer to 5 m / s. Add the three solutions to the stirrer at the same time at a flow rate of 92 ml / min, 100 ml / min and 5 ml / min respectively. After the reaction is completed, age at 90℃ for 2 hours to obtain a white slurry.

[0042] During filtration, the speed and feed rate of the vacuum belt filter are adjusted to form a filter cake thickness of 0.5 cm. Then, the filter cake is washed with high-temperature pure water at 90°C. The volume ratio of pure water to slurry is 4:1. After washing, water is added again to make slurry. The slurry is spray-dried at a drying temperature of 250°C to obtain loose and porous precursor particles. Then, it is calcined at 1150°C for 4 hours to obtain zirconium oxide powder.

[0043] Zirconia powder and 90°C high-temperature pure water were added to a high-speed mixing tank with a mass ratio of 1:2. Simultaneously, carbon dioxide gas at a flow rate of 10 L / min was introduced into the solution. After stirring for 30 min, the mixture was allowed to stand for 2 h. The supernatant was then separated, and water was added to obtain a zirconia slurry. The slurry was then milled and spray-granulated to obtain zirconia granulated powder. The chloride ion content of the obtained granulated powder was less than 2 ppm.

[0044] Example 2

[0045] First, prepare an aqueous solution of 1 mol / L zirconium oxychloride, 2 mol / L ammonia and 0.75 mol / L yttrium chloride. Turn on the stirrer in the reactor and adjust the linear speed of the stirrer to 6 m / s. Add the three solutions to the reactor at the same time at flow rates of 92 ml / min, 96 ml / min and 3.68 ml / min respectively. After the reaction is completed, age at 90℃ for 2 hours to obtain a white slurry.

[0046] During filtration, the speed and feed rate of the vacuum belt filter are adjusted to make the filter cake thickness 1cm. Then, the filter cake is washed with high-temperature pure water at 80℃, with a volume ratio of pure water to slurry of 3:1. After washing, water is added again to make slurry. Spray drying is performed at a drying temperature of 250℃ to obtain loose and porous precursor particles, which are then calcined at 1150℃ for 8 hours to obtain zirconium oxide powder.

[0047] Zirconia powder and 80°C high-temperature pure water were added to a high-speed mixing tank with a mass ratio of 1:5. Simultaneously, carbon dioxide gas at a flow rate of 10 L / min was introduced into the solution. After stirring for 5 minutes, the mixture was allowed to stand for 4 hours. The supernatant was then separated, and water was added to obtain a zirconia slurry. The slurry was then milled and spray-granulated to obtain zirconia granulated powder. The chloride ion content of the obtained granulated powder was less than 5 ppm.

[0048] Example 3

[0049] First, prepare an aqueous solution of 1 mol / L zirconium oxychloride, 2 mol / L ammonia and 0.75 mol / L yttrium chloride. Turn on the stirrer in the reactor and adjust the linear speed of the stirrer to 2 m / s. Add the three solutions to the reactor at the same flow rates of 92 ml / min, 265 ml / min and 12.27 ml / min respectively. After the reaction is completed, age at 90℃ for 2 hours to obtain a white slurry.

[0050] During filtration, the speed and feed rate of the vacuum belt filter are adjusted to make the filter cake thickness 1cm. Then, the filter cake is washed with high-temperature pure water at 70℃, with a volume ratio of pure water to slurry of 1:1. After washing, water is added again to make slurry. At a drying temperature of 200℃, it is spray-dried to obtain loose and porous precursor particles, which are then calcined at 1300℃ for 4 hours to obtain zirconium oxide powder.

[0051] Zirconia powder and 70°C high-temperature pure water were added to a high-speed mixing tank with a mass ratio of 2:1. Simultaneously, carbon dioxide gas at a flow rate of 5L / min was introduced into the solution. After stirring for 30 minutes, the mixture was allowed to stand for 2 hours. The supernatant was then separated, and water was added to obtain a zirconia slurry. The slurry was then milled and spray-granulated to obtain zirconia granulated powder. The chloride ion content of the obtained granulated powder was less than 8ppm.

[0052] Comparative Example 1

[0053] First, prepare an aqueous solution of 1 mol / L zirconium oxychloride, 2 mol / L ammonia and 0.75 mol / L yttrium chloride. Turn on the stirrer and adjust the linear speed of the stirrer to 5 m / s. Add the three solutions to the stirrer at the same time at a flow rate of 92 ml / min, 100 ml / min and 5 ml / min respectively. After the reaction is completed, age at 90℃ for 2 hours to obtain a white slurry.

[0054] During filtration, the speed and feed rate of the vacuum belt filter are adjusted to form a filter cake thickness of 0.5 cm. Then, the filter cake is washed with pure water at 25°C, with a volume ratio of pure water to slurry of 4:1. After washing, water is added again to form a slurry. The slurry is then spray-dried at 250°C to obtain loose and porous precursor particles, which are then calcined at 1150°C for 4 hours to obtain zirconium oxide powder.

[0055] Zirconia powder and 90°C high-temperature pure water were added to a high-speed mixing tank with a mass ratio of 1:2. Simultaneously, carbon dioxide gas at a flow rate of 10 L / min was introduced into the solution. After stirring for 30 min, the mixture was allowed to stand for 2 h. The supernatant was then separated, and water was added to obtain a zirconia slurry. The slurry was then milled and spray-granulated to obtain zirconia granulated powder. The chloride ion content of the obtained granulated powder was 1000 ppm.

[0056] Comparative Example 2

[0057] First, prepare an aqueous solution of 1 mol / L zirconium oxychloride, 2 mol / L ammonia and 0.75 mol / L yttrium chloride. Turn on the stirrer in the reactor and adjust the linear speed of the stirrer to 1 m / s. Add the three solutions to the reactor at the same time at flow rates of 92 ml / min, 96 ml / min and 3.68 ml / min respectively. After the reaction is completed, age at 90℃ for 2 hours to obtain a white slurry.

[0058] During filtration, the speed and feed rate of the vacuum belt filter are adjusted to make the filter cake thickness 1cm. Then, the filter cake is washed with high-temperature pure water at 80℃, with a volume ratio of pure water to slurry of 3:1. After washing, water is added again to make slurry. Spray drying is performed at a drying temperature of 250℃ to obtain loose and porous precursor particles, which are then calcined at 1150℃ for 8 hours to obtain zirconium oxide powder.

[0059] Zirconia powder and 80°C high-temperature pure water were added to a high-speed mixing tank with a mass ratio of 1:5. Simultaneously, carbon dioxide gas at a flow rate of 10 L / min was introduced into the solution. After stirring for 5 minutes, the mixture was allowed to stand for 4 hours. The supernatant was then separated, and water was added to obtain a zirconia slurry. The slurry was then milled and spray-granulated to obtain zirconia granulated powder. The chloride ion content of the obtained granulated powder was 300 ppm.

[0060] Comparative Example 3

[0061] First, prepare an aqueous solution of 1 mol / L zirconium oxychloride, 2 mol / L ammonia and 0.75 mol / L yttrium chloride. Turn on the stirrer in the reactor and adjust the linear speed of the stirrer to 6 m / s. Add the three solutions to the reactor at the same time at flow rates of 92 ml / min, 96 ml / min and 3.68 ml / min respectively. After the reaction is completed, age at 90℃ for 2 hours to obtain a white slurry.

[0062] During filtration, the speed and feed rate of the vacuum belt filter are adjusted to make the filter cake thickness 1cm. Then, the filter cake is washed with high-temperature pure water at 80℃, with a volume ratio of pure water to slurry of 3:1. After washing, water is added again to make slurry. Spray drying is performed at a drying temperature of 250℃ to obtain loose and porous precursor particles, which are then calcined at 1150℃ for 8 hours to obtain zirconium oxide powder.

[0063] Zirconia powder and 80°C high-temperature pure water were added to a high-speed mixing tank. The mass ratio of zirconia to pure water was 1:5. No carbon dioxide gas was introduced at this time. After stirring for 5 minutes, the mixture was allowed to stand for 4 hours. Then, the supernatant was separated, and water was added to obtain zirconia slurry. Zirconia granulated powder was obtained by sand milling and spray granulation. The chloride ion content of the obtained granulated powder was less than 500 ppm.

Claims

1. A method for preparing zirconia granulated powder with low chloride ion content, characterized in that, Includes the following steps: (1) Prepare an aqueous solution containing zirconium salt, yttrium salt and precipitant, and then add the three solutions to the reaction vessel at a certain flow rate. Adjust the linear velocity of the stirrer to 2-6 m / s. After the reaction is completed, age the mixture to obtain a white slurry. (2) Wash the white slurry at a temperature of 70-90℃, spray dry to obtain a loose and porous precursor powder, and then calcine it at a high temperature to obtain zirconium oxide powder. (3) Add a certain proportion of zirconia powder and pure water to a high-speed mixing tank. The temperature of the pure water is 70-90℃. At the same time, carbon dioxide gas is introduced into the solution at a flow rate of 5-10L / min. Stir and wash the powder, then let it stand to separate the supernatant, and finally add pure water to obtain zirconia slurry. (4) The zirconium oxide slurry is sand-milled and spray-granulated to obtain zirconium oxide granulated powder with low chloride ion content.

2. The preparation method according to claim 1, characterized in that, The zirconium salt mentioned in step (1) is selected from at least one of zirconium oxychloride, zirconium nitrate, and zirconium sulfate; the yttrium salt is selected from at least one of yttrium chloride, yttrium nitrate, and yttrium sulfate; and the precipitant is selected from at least one of ammonia, urea, ammonium carbonate, or ammonium bicarbonate.

3. The preparation method according to claim 2, characterized in that, The zirconium salt mentioned in step (1) is zirconium oxychloride; the yttrium salt is yttrium chloride; and the precipitant is ammonia.

4. The preparation method according to any one of claims 1-3, characterized in that, The molar ratio of the aqueous solutions of zirconium salt, yttrium salt and precipitant mentioned in step (1) is 1:0.03-0.1:2-5.

5. The preparation method according to claim 4, characterized in that, In step (1), the aging temperature is 75-95℃ and the aging time is 1-4h.

6. The preparation method according to claim 1, characterized in that, In step (2), the washing medium is pure water, and the volume ratio of the washing medium to the slurry is (1-4):

1.

7. The preparation method according to claim 6, characterized in that, The washing equipment used in step (2) is a vacuum belt filter, and the filter cake thickness during washing is 0.1-1cm.

8. The preparation method according to claim 1, 6, or 7, characterized in that, The spray drying temperature in step (2) is 200-250℃.

9. The preparation method according to claim 8, characterized in that, The precursor powder obtained after drying is a loose and porous spherical particle with an average particle size of 30-150 μm.

10. The preparation method according to claim 1, characterized in that, The high-temperature calcination temperature in step (2) is 1150℃~1300℃, and the calcination time is 4h~8h.

11. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of zirconium oxide powder to pure water is (0.2-2):

1.

12. The preparation method according to claim 1, characterized in that, In step (3), the stirring time is 5-30 min and the standing time is 0.5-4 h.

13. The preparation method according to claim 1, characterized in that, The chloride ion content in the zirconium oxide granulated powder obtained in step (4) is less than 10 ppm.

Citation Information

Patent Citations

  • Production of superfine mono-dispered nano-zirconium dioxide

    CN101074116B

  • Method for removing Cl <-> in zirconium oxide powder

    CN112811903A

  • Method for producing nano composite zirconium oxide powder by hydrothermal method

    CN114014651A